Pendampingan Penyusunan Buku Materi Ajar Arabic Writing Dalam Rangka Meningkatkan Efektifitas Pembelajaran TPQ - Wildan Habibi; Doni Saputra; Muhammad Syahrul Munir; Ulul Hikam (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2025)
This study aims to assist the process of compiling the Arabic Writing book as a creative effort in developing learning media for writing the hijaiyah letters at TPQ Al Hidayah, Sidorejo,Medowo Village. The background of this study is the low ability of TPQ children in writing Arabic letters correctly, as well as the limited teaching materials that are appropriate to their developmental stage. The study used the Participatory Action Research (PAR) method which emphasizes active collaboration between researchers, teachers, and parents in every stage of the activity. Data were obtained through observation, interviews, documentation, and direct participation in the process of compiling and implementing the book. The results of the study show that the mentoring was carried out through several stages, namely identifying needs, preparing a book draft, limited trials, and evaluation. The implementation of the program produced significant impacts that were seen as children experiencing increased skills in writing the hijaiyah letters, teachers gaining experience in designing innovative teaching materials, and parents being helped in accompanying children learning at home. The success of this mentoring program was supported by community participation and a good cooperation model between all elements involved